Impacts of weather, work rate, hydration, and clothing in heat‐related illness in California farmworkers. Issue 12 (9th April 2019) - Vega‐Arroyo, Alondra J.; Mitchell, Diane C.; Castro, Javier R.; Armitage, Tracey L.; Tancredi, Daniel J.; Bennett, Deborah H.; Schenker, Marc B.
Abstract: Background: The primary aim of this study was to investigate the effects of work rate, hydration status, and clothing on core body temperature (CBT) on California farmworkers. Methods: Two hundred and eighty‐seven farmworkers were recruited in Summer 2015, with 259 participants having sufficient data for analysis. We collected CBT, ambient temperature, work rate, body weight loss, and clothing worn by each participant throughout the work day and demographic data from a questionnaire. Results: Multiple regression with CBT as the outcome was used to determine the adjusted associations between CBT, environmental heat load, and worker characteristics. The multivariate regression model showed statistically significant associations of CBT with work rate ( β  = .006, 95% CI [0.004, 0.009]) and wet‐bulb globe temperature ( β  = .03, 95% CI [0.017, 0.05]). Conclusion: Results suggest that among our population workload is the primary modifiable risk factor for heat‐related illness. As expected, the ambient temperature was also associated with higher risk.